2020
DOI: 10.3390/cancers12020440
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stromal Cell-Derived IL-8 Upregulates PVR Expression on Multiple Myeloma Cells via NF-kB Transcription Factor

Abstract: Bone marrow stromal cells (BMSCs) strongly contribute to multiple myeloma (MM) progression, promoting the survival and growth of malignant plasma cells (PCs). However, the possible impact of these cells on the immune-mediated recognition of MM cells remains largely unknown. DNAM-1 activating receptor plays a prominent role in NK cell anti-MM response engaging the ligands poliovirus receptor (PVR) and nectin-2 on malignant PCs. Here, we analysed the role of MM patient-derived BMSCs in the regulation of PVR expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…NK cells of peripheral blood mononuclear cell origin from healthy donors were incubated with SKO-007 (J3) cells (Human myeloma cells), some of which were untreated and some of which were incubated with BMSC-CM for 72h, as target cells for degranulation assay. The results showed that CD107a expression was signi cantly elevated in the combined BMSC incubation group, indicating enhanced degranulation of NK cells, and the same results were also observed in patient-derived NK cells against SKO-007 (J3) cells or autologous CD138+ plasma cells treated with BMSC-CM (79). Bone marrow MSCs also modulate the immune activity of hepatic NK cells, and Con A (Concanavalin A) was injected into C57 to model Con A liver injury.…”
Section: Nk Cellsmentioning
confidence: 57%
“…NK cells of peripheral blood mononuclear cell origin from healthy donors were incubated with SKO-007 (J3) cells (Human myeloma cells), some of which were untreated and some of which were incubated with BMSC-CM for 72h, as target cells for degranulation assay. The results showed that CD107a expression was signi cantly elevated in the combined BMSC incubation group, indicating enhanced degranulation of NK cells, and the same results were also observed in patient-derived NK cells against SKO-007 (J3) cells or autologous CD138+ plasma cells treated with BMSC-CM (79). Bone marrow MSCs also modulate the immune activity of hepatic NK cells, and Con A (Concanavalin A) was injected into C57 to model Con A liver injury.…”
Section: Nk Cellsmentioning
confidence: 57%
“…In particular, the complex interaction with bone marrow stromal cells (BMSCs) strongly supports the survival, proliferation and migration of malignant PCs and promotes osteoclastogenesis and angiogenesis. Mekhloufi et al disclosed a previously unknown immune regulatory role of BMSCs, capable of tuning MM PCs-NK cells cross-talk; in fact, IL-8 secretion by BMSCs triggered an NF-κB dependent expression of PVR ligands on MM PCs, in turn promoting DNAM-1 receptors' recognition and NK cell degranulation [1].…”
Section: Signals Arising From the MM Bone Marrow Microenvironment (Bmm)mentioning
confidence: 99%
“…PVR is also a ligand recognized by the AR DNAM-1 that is expressed on NK cells. DNAM-1 has been shown to play a prominent role in NK cell-mediated anti-MM response ( 191 ). While TIGIT expression is increased in MM patients, DNAM-1 expression is decreased ( 192 ).…”
Section: Nk Cell Irsmentioning
confidence: 99%
“…Furthermore, co-expression of TIGIT with either PD-1 or TIM-3 has been correlated with a dysfunctional phenotype in TILs ( 195 ). Additional studies have shown that PVR expression can be induced by chemotherapy ( 192 ) or by IL-8 signaling through the CXCR1/CXCR2 axis ( 191 ), suggesting that a combination of anti-TIGIT mAbs with chemotherapy may be beneficial when patients’ immune cells have TIGIT expression.…”
Section: Nk Cell Irsmentioning
confidence: 99%
See 1 more Smart Citation